Agrarian Reform and Conflict Resolution: The Role of GTRA in the Case of Sumberklampok Village, Buleleng Regency - Sudiarta, I Made; Talakua, Jossh Christheyn Endrew (Sekolah Tinggi Pertanahan Nasional, 2025)
This study investigates the development of Sumberklampok Village in its struggle related to the conflict to obtain land rights. This study describes the chronology of the existence of Sumberklampok Village among various entities, as well as the role of the agreement between the Bali Provincial Government and the community in granting rights to part of the ex-HGU land. Using a case study approach in obtaining field data, the author's findings show that the community has been fighting for land rights that have been controlled for decades. The community has implemented land redistribution activities, leading to the designation of Sumberklampok Village as the National Agrarian Reform Master Project. The implications of the agreement include active community participation in land management, improved community welfare, transparent management and supervision, necessary counselling and assistance for the community, and attention to environmental aspects in land management. The conclusion is that the implementation of the ex-HGU land redistribution agreement is important to ensure fair use of natural resources for the community and sustainable improvement of community welfare. This study presents a series of policy recommendations, including monitoring the impact of land redistribution on community welfare, increasing transparency and efficiency of land management, strengthening education and counselling for the community, and environmental protection in land management.